On the development of reflexive learning in the pedagogical process of higher education institutions - Кажикенова, Гульнар; Нургалиева, Муршида; Кодекова, Галия (Pedagogy and Psychology, 2022)
This article is devoted to the study of the problems of reflexive learning in the pedagogical process of higher education institutions. The main method of descriptive research is the questionnaire method. The questionnaires developed by us for studying the reflexive activity of students relate to the following aspects: a) self-knowledge, b) correlation of experience with knowledge, c) self-reflection, and d) self-regulation of learning processes. The questionnaires were submitted to students of various specialties studying the disciplines of the relevant educational programs (social work, pedagogy and psychology). In particular, the objectives of the questionnaire aimed at determining the students ' assessment of the process of reflexive learning are as follows: 1) determine how much students evaluate the methods of reflexive learning used in the process of reflexive activity; 2) identify the main difficulties faced by students when integrating reflexive learning methods into the process of reflexive activity, and 3) identify how effective the methods used were and their impact on the development of self-reflection and self-regulation of learning processes.